Potencial biomodificador e estabilidade de união à dentina de compostos inspirados na adesividade subaquática - Pascoal, Samuel Chillavert Dias (2024)
The present study consists of two chapters. The first chapter aimed to evaluate, by means of a systematic review and meta-analysis, the effect of bioinspired mussel adhesive primers on the stability of the resin-dentin interface. The review followed the PRISMA guidelines and was carried out between July 13, 2023 and March 13, 2024. Databases such as PubMed, SCOPUS, Web of Science, EMBASE, Lilacs, LIVIVO and Google Scholar were used. Eligibility criteria included in vitro trials, human dentin as a substrate, use of mussel-inspired primers, presence of a control group, and evaluation of bond strength by microtensile bonding after ageing. Two independent reviewers identified 5.124 articles, of which 7 were selected. The RoBDEMAT tool analyzed the risk of bias. Most studies used the etch-and-wash adhesive system, highlighting the need to evaluate mussel-inspired monomers in different adhesive strategies. The meta-analysis showed a significant increase in dentin bond strength with mussel-inspired monomers after thermocycling, despite high heterogeneity. The results suggest that these monomers, especially when incorporated into adhesive formulations, promote dentin bond stability. The second chapter evaluated the biomodifying potential and dentin bond strength of molecules inspired by underwater adhesion as dentin pretreatments. The dependent variables included modulus of elasticity (ME) (n=15), mass change (MV) and biodegradation rates (BD%) (n=15), chemical analysis by Fourier transform infrared spectroscopy (n=3) [FTIR], and bond strength by microtensile strength (n=10) [RU]. Nanoleakage (n=3) and micropermeability (n=3) analyses were also performed. The independent variables were three concentrations of phosphoserine at 1 mmol/L (pSer1), 5 mmol/L (pSer5) and 10 mmol/L (pSer10), 3,4-dihydroxyphenylalanine at 5 mmol/L (DOPA5), grape seed extract at 6.5% (GSE6.5) and distilled water (DW). TBS and BD% were carried out immediately and after 6 months of storage. The GSE6.5 group showed higher ME values and gain after biomodification, with no statistical difference with pSer10. GSE6.5 and pSer10 showed positive MV values, while DOPA maintained integrity in degradation rates. The pSer10 group showed the highest absorbance peaks in the chemical analysis, compared to all the groups. Regarding immediate RU, all the pSer groups showed similar values to each other and to the DOPA and GSE6.5 groups. After storage, pSer1 and pSer5 were similar to GSE6.5. All the groups showed stability in bond strength after 6 months of storage, with the exception of pSer10. In terms of nanoleakage, all pSer groups showed significantly less deposition of silver nitrate compared to DW, GSE6.5 and DOPA. With regard to micropermeability, the pSer1 and 5 groups showed greater adhesive interface integrity with the infiltration of resin tags into the dentin substrate, in contrast to the DW, GSE6.5 and pSer10 groups, in which "water trees", gaps and fluorescein infiltration were observed. It can be concluded that the biomodifying potential of these compounds presented as inconsistent, pSer at concentrations of 1 and 5 mM was able to promote bond stability after storage in distilled water, maintaining the integrity of the resin-dentin interface.